2013
DOI: 10.1590/s0102-79722013000100008
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of psychometric properties of an inventory of teachers' perceptions on socio-emotional needs

Abstract: The objective of this study was to evaluate the psychometric properties of an assessment instrument on teachers' perceptions regarding the development of socio-emotional skills. Results revealed a consistent four-factor structure (School/teachers' needs for socio-emotional skills promotion; Needs regarding teaching-learning process; Difficulties in dealing with students' socio-emotional deficits, Socio-emotional needs related to teacher's initial training) with internal consistency values above .79. Confirmato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
4
0
3
Order By: Relevance
“…In that study, being female predicted stronger efficacy for enabling student engagement, classroom management, and instructional strategies. Recently, in a study of 266 Portugese teachers, Moreira, Pinheiro, Gomes, Cotter and Ferreira (2013) found that male teachers reported significantly greater difficulties than female teachers in promoting students' socialemotional skills. Meanwhile, in the relatively new research field about the impact of cyberbullying on students' wellbeing, Eden, Heiman and Olenik-Shemesh, (2013) reported a study that administered a questionnaire about cyberbullying to 328 Israeli teachers from diverse school settings.…”
Section: Teachers Are At the Core Of Promoting Mental Health In Schoolsmentioning
confidence: 99%
“…In that study, being female predicted stronger efficacy for enabling student engagement, classroom management, and instructional strategies. Recently, in a study of 266 Portugese teachers, Moreira, Pinheiro, Gomes, Cotter and Ferreira (2013) found that male teachers reported significantly greater difficulties than female teachers in promoting students' socialemotional skills. Meanwhile, in the relatively new research field about the impact of cyberbullying on students' wellbeing, Eden, Heiman and Olenik-Shemesh, (2013) reported a study that administered a questionnaire about cyberbullying to 328 Israeli teachers from diverse school settings.…”
Section: Teachers Are At the Core Of Promoting Mental Health In Schoolsmentioning
confidence: 99%
“…Gomes et al (2010) encontrou o mesmo resultado em sua pesquisa e concluiu que quanto maior a carga horária realizada e o número de alunos em sala, essa distância aluno--professor tende a aumentar conjuntamente com a exaustão emocional/estresse e há uma diminuição do sentimento de realização profissional do docente. Esta situação acaba por prejudicar não apenas a saúde mental e física do educador, mas também ao aluno e a instituição escolar, podendo acarretar até mesmo no abandono da profissão pelo professor (LE-MOS, 2009;MOREIRA et al, 2013). Na Malásia, uma pesquisa com 580 professores de ensino secundário inves tigou a prevalência de estresse e fatores associados que podem contribuir com este quadro.…”
Section: Discussionunclassified
“…Moreover, due to the need of schools to consider the students in a biopsychosocial perspective (Moreira, Oliveira et al, 2012;Moreira, Crusellas, Sá, Gomes, & Matias, 2010), this instrument has the potential to contribute to the understanding of how these dimensions relate to other relevant school-or teacher-related dimensions (e.g. Moreira, Pinheiro, Gomes, Cotter, & Ferreira, 2013).…”
Section: Discussionmentioning
confidence: 99%